In-Silico approach for identification of effective and stable inhibitors for COVID-19 main protease (Mpro) from flavonoid based phytochemical constituents of Calendula officinalis. Issue 16 (2nd November 2021) - Das, Pratik; Majumder, Ranabir; Mandal, Mahitosh; Basak, Piyali
Abstract: The recent outbreak of the coronavirus disease COVID-19 is putting the world towards a great threat. A recent study revealed COVID-19 main protease (M pro ) is responsible for the proteolytic mutation of this virus and is essential for its life cycle. Thus inhibition of this protease will eventually lead to the destruction of this virus. In-Silico Molecular docking was performed with the Native ligand and the 15 flavonoid based phytochemicals of Calendula officinals to check their binding affinity towards the COVID-19 main protease. Finally, the top 3 compounds with the highest affinity have been chosen for molecular dynamics simulation to analyses their dynamic properties and conformational flexibility or stability. In-Silico Docking showed that major phytochemicals of Calendula officinals i.e. rutin, isorhamnetin-3-O-β-D, calendoflaside, narcissin, calendulaglycoside B, calenduloside, calendoflavoside have better binding energy than the native ligand (inhibitor N3). MD simulation of 100 ns revealed that all the protease-ligand docked complexes are overall stable as compare to M pro -native ligand (inhibitor N3) complex. Overall, rutin and caledoflaside showed better stability, compactness, and flexibility. Our i n silico (Virtual molecular docking and Molecular dynamics simulation) studies pointed out that flavonoid based phytochemicals of calendula (rutin, isorhamnetin-3-O-β-D, calendoflaside) may be highly effective for inhibiting M pro which is the main protease for SARS-CoV-2 causing the deadly disease COVID-19. Rutin is already used as a drug and the other two compounds can be made available for future use. Thus the study points a way to combat COVID-19 by the use of major flavonoid based phytochemicals of Calendula officinals. Communicated by Ramaswamy H. Sarma